Bibliografie specjalne Wojewódzkiej Biblioteki Publicznej - Książnicy Kopernikańskiej w Toruniu = Special bibliographies of the Provincial Public Library - The Copernicus Library in Toruń - Broda, Anna; Kulig, Katarzyna (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The Provincial Public Library - the Copernicus Library in Toruń, established in 1923, is an institution of great importance for the social and cultural life of Toruń and the whole region. Its Information and Bibliographic Department hasset itself the task of recording information about the activities of the Copernicus Library, its impact on the local community and the people associated with it. The department's staff began compiling two special bibliographies: "Bibliography ofthe Provincial Public Library - the Copernicus Library in Toruń" and "Bibliography of the employees of the Regional Public Library - Copernicus Library inToruń". Both bibliographies are to become a complete database of existing materials related to the library, thus serving both researchers of the history of the institution and users interested in the history of the Provincial Public Library - The Copernicus Library in Toruń.
Keywords: biblioteki publiczne; bibliografie specjalne; bibliotekarze; Toruń; Wojewódzka Biblioteka Publiczna - Książnica Kopernikańska w Toruniu; public libraries; special bibliographies; librarians; the Provincial Public Library - The Copernicus Library in Toruń